Ballistic Limit Estimation Approaches for Ballistic Resistance Assessment - Tahenti, Beya; Coghe, Frederik; Nasri, Rachid (Defence Science Journal, 2020)
The armour technologist conducts ballistic impact testing either for evaluating armour materials and systems or for studying material’s defeating mechanism. Most standards make use of the ballistic limit velocity for ballistic assessment. This is the bullet impact velocity that leads to the protection perforation in 50 per cent of the cases. Various models have been emerged to estimate this key metric. The present article summarises the popular models developed for ballistic limit estimation. An attempt is made to point out models’ strength and weakness. First, the experimental set-up used for that goal is displayed. Next, a concise overview of ballistic limit estimation methods is presented. Lastly, a discussion is dedicated to model’s comparison and analysis. This literature survey reveals that the main drawback of already existing methods is that they are purely statistical. Moreover, existing methods are based on the normality assumption of perforation velocities which tends from -infinity to infinity. The main conclusion of this survey is that the presented methods offer a comparable accuracy in estimating the ballistic limit velocity. However, a given variability is remarked when extreme values estimation is of interest, impact velocities leading to low and high perforation probability. Finally, existing models’ performances decay with the reduction of the experimental sample size which represent a constraining requirement in ballistic resistance assessment.